Cosmosycanus perelegans (Hemiptera: Reduviidae: Harpactorinae), a new record from China, with report of its female genitalia - Zhao, Ping; Ren, Shuzhi; Wang, Baohai; Cai, Wanzhi (Zootaxa, 2015)
The oriental genus Cosmosycanus Ishikawa & Tomokuni, 2004 and the species Cosmosycanus perelegans (Breddin, 1903) are newly  recorded from China. Cosmosycanus perelegans is redescribed and  illustrated. The female genitalia is reported for the first time. The variations of colour patterns and male genital structures among Chinese and Vietnamese individuals are briefly noted.